2009
DOI: 10.1375/twin.12.1.63
|View full text |Cite
|
Sign up to set email alerts
|

The Australian Twin Study of Gambling (OZ-GAM): Rationale, Sample Description, Predictors of Participation, and a First Look at Sources of Individual Differences in Gambling Involvement

Abstract: T wo major challenges to conducting a communitybased twin study of pathological gambling (PG) disorder are that: (a) it is relatively rare, and (b) individuals with the disorder in the community may be difficult to locate and recruit. We describe a new study of 4,764 individuals recruited from the Australian Twin Registry in which we attempt to effectively deal with the first challenge and examine the impact of the second challenge. The lifetime prevalence of DSM-IV PG in this Australian twin sample was 2.2%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
100
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(108 citation statements)
references
References 34 publications
4
100
3
Order By: Relevance
“…When the average per capita gambling expenditure as a percentage of net disposable income in 2003 was estimated for 21 industrialized nations (Pryor, 2008), Australia was ranked first and the United States was ranked 14th among the countries included, with 5.9% and 1.8% of their average per capita net disposable incomes spent on gambling, respectively. In the three US epidemiologic surveys noted above, the NESARC, GIBS, and NCS-R, the lifetime prevalences of DSM-IV PG were 0.43% (Slutske, 2006a), 0.80% (Slutske, 2006a), and 0.60% (Kessler et al, 2008), respectively, compared to 2.2% in this Australian national survey (Slutske et al, 2009). Australia is an ideal setting in which to conduct a community-based epidemiologic study of recovery, treatment-seeking, and natural recovery in PG.…”
contrasting
confidence: 54%
See 2 more Smart Citations
“…When the average per capita gambling expenditure as a percentage of net disposable income in 2003 was estimated for 21 industrialized nations (Pryor, 2008), Australia was ranked first and the United States was ranked 14th among the countries included, with 5.9% and 1.8% of their average per capita net disposable incomes spent on gambling, respectively. In the three US epidemiologic surveys noted above, the NESARC, GIBS, and NCS-R, the lifetime prevalences of DSM-IV PG were 0.43% (Slutske, 2006a), 0.80% (Slutske, 2006a), and 0.60% (Kessler et al, 2008), respectively, compared to 2.2% in this Australian national survey (Slutske et al, 2009). Australia is an ideal setting in which to conduct a community-based epidemiologic study of recovery, treatment-seeking, and natural recovery in PG.…”
contrasting
confidence: 54%
“…Although this method of ascertainment does not necessarily yield a sample that can be considered truly 'representative' of the population of Australia, it covers a broader range of socioeconomic backgrounds and range of psychopathology than would be typical for most community-based volunteer samples. Indeed, an examination of the characteristics of the sample suggests that it is broadly representative of Australian individuals 32 to 43 years of age (Slutske et al, 2009). In a previous paper (Slutske et al, 2009), a number of predictors of non-participation were identified, including PG, but these did not have a large net effect on the estimated number of individuals with PG in the sample.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…They were first surveyed in [1989][1990][1991][1992]. Data in the current study were collected in 2004-2007, for a study primarily focused on gambling (Slutske et al 2009), via structured diagnostic telephone interview and mailed self-report questionnaire [interview: n = 4764 twins, mean age = 37.7 years (range = 32-43), response rate = 80%; questionnaire: n = 4369 twins, response rate = 92%]. The current study was based on data from same-sex monozygotic (MZ) and dizygotic (DZ) twins.…”
Section: Participantsmentioning
confidence: 99%
“…During the second wave of the study 4764 people participated. In addition to telephone interviews, respondents also completed questionnaires received by mail [17]. One study carrying out a genetic association study (to be discussed later), also used this dataset [18].…”
Section: Samples Of Twin Studiesmentioning
confidence: 99%